2019
DOI: 10.1373/clinchem.2018.297028
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Circulating Tumor Cells in Patients with Merkel Cell Carcinoma

Abstract: BACKGROUND Merkel cell carcinoma (MCC) is a rare, aggressive skin cancer with increasing incidence and high mortality rates. MCC has recently become the subject of immune checkpoint therapy, but reliable biomarkers for estimating prognosis, risk stratification, and prediction of response are missing. METHODS Circulating tumor cells (CTCs) were detected in peripheral blood from patients with MCC by use of the CellSearch® syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 45 publications
0
18
0
3
Order By: Relevance
“…Two previous studies on CTC detection in MCC with the CellSearch system identified CTCs in 41% of the tested patients 27,28 . On the other hand, the Maintrac technology, based on the EpCAM/CD56 or CK20 markers for CTC detection, identified CTCs in up to 90% of patients.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Two previous studies on CTC detection in MCC with the CellSearch system identified CTCs in 41% of the tested patients 27,28 . On the other hand, the Maintrac technology, based on the EpCAM/CD56 or CK20 markers for CTC detection, identified CTCs in up to 90% of patients.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, CTCs have been included as prognostic markers in MCC. Three recent studies addressed CTC detection in MCC [26][27][28] , two using positive selection strategy for CTC enrichment before their detection and one using erythrocytes lysis. Conversely, our study compared two different complementary methods for CTC detection in MCC: (i) the CellSearch system, the only FDA-cleared technology for metastatic breast, prostate and colon cancer [17][18][19] , and (ii) the RosetteSep and DEPArray (R-D) workflow, where CTC detection is based on negative enrichment (leukocyte depletion) followed by CTC detection by DEPArray that also allows the direct sorting of single CTCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include immunoaffinity analysis (for markers including EpCAM, CD15, CD45, and CD66b); techniques for the analysis of biophysical characteristics such as size, deformability, density, and surface charge; immunofluorescence for quantification; and molecular techniques including sequence analysis for genomics and transcriptomics, mass cytometry for proteomic analysis, and targeted bisulfite sequencing for epigenetic analysis . Table highlights the potential of CTCs as biomarkers for disease progression, prognosis, and outcomes for a wide range of cancers . Figure summarizes the potential prognostic role of CTCs at various stages of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…4 Table 1 highlights the potential of CTCs as biomarkers for disease progression, prognosis, and outcomes for a wide range of cancers. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] Figure 1 summarizes the potential prognostic role of CTCs at various stages of cancer.…”
Section: Introductionmentioning
confidence: 99%